Online Learning with Project Based Learning Model to Increase Student HOTS in Waves and Optical Courses - Hikmawati Hikmawati (Jurnal Ilmiah Profesi Pendidikan, 2022)
Higher Order Thinking Skills (HOTS) is one of the competencies that must be trained from early childhood to university so that students can compete globally. The facts show that the competence of students in Indonesia is still classified at the LOTS level. Therefore, various efforts are needed to improve the competence of students so that the level of competency they have can increase. This research aims to increase student HOTS in Waves and Optics courses through online lectures using the Project Based Learning (PjBL) model. This research was conducted in 5 meetings, from April 19 2022 to May 31 2022. The research subjects consisted of 27 students who took Waves and Optics lectures in Class IV-B, in the Physics Education Study Program, University of Mataram, Academic Year 2021/2022. The research instrument for obtaining HOTS score data is an essay test given at the beginning of the meeting and at the end of the meeting. The increase in HOTS scores is calculated using the N-gain test. The results showed that the average HOTS score of students in the initial test was 55, while in the final test it was 79. The N-gain score was 54 which is included in the medium category. Thus, it can be concluded that online lectures using the Project Based Learning model in the Waves and Optics course increase the HOTS scores of prospective physics teacher students.